1988
DOI: 10.1002/jnr.490200204
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a human glial fibrillary acidic protein cDNA: A tool for the molecular analysis of reactive gliosis in the mammalian central nervous system

Abstract: Two clones encoding human glial fibrillary acidic protein (GFAP) were isolated from a human astrocytoma cDNA library. The clones pHGFAP1 and pHGFAP2 were selected by the combined use of differential colony hybridization and hybridization-selection technique with polyclonal anti GFAP antiserum. The longer one, pHGFAP1, encompasses 3.0 kb and includes the 1.8 kb long 3' untranslated region specific to the human mRNA. Sequence data disclosed an extensive homology within the coding region of human and mouse GFAP c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
25
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 44 publications
5
25
0
Order By: Relevance
“…Geisler and Weber (8) have sequenced =50o of the porcine GFAP (pGFAP) protein, and partial cDNA and genomic molecular clones of murine GFAP (mGFAP) have been evaluated (9,10). Also, partial DNA sequence data have been reported for hGFAP, corresponding to regions coding for the rod domain (11,12). As anticipated, our data document considerable homology between GFAPs from different species.…”
supporting
confidence: 67%
“…Geisler and Weber (8) have sequenced =50o of the porcine GFAP (pGFAP) protein, and partial cDNA and genomic molecular clones of murine GFAP (mGFAP) have been evaluated (9,10). Also, partial DNA sequence data have been reported for hGFAP, corresponding to regions coding for the rod domain (11,12). As anticipated, our data document considerable homology between GFAPs from different species.…”
supporting
confidence: 67%
“…It has been suggested that expression of the proenkephalin gene may be an early marker for gliosis (Melner et al, 1990;Rataboul et al, 1988). Because the present studies demonstrate the involvement of an injury-inducible cytokine in regulation of opioid genes, this in vitro system could prove useful in the design and evaluation of pharmacological agents aimed at modulating such cellular behaviors.…”
Section: Discussionmentioning
confidence: 94%
“…The glial scar has traditionally been regarded as inhibitory to axon regeneration. GFAP expression was regarded as a sensitive and reliable marker labeling reactive astrocytes responding to CNS injuries [35,36]. Other molecular markers that have been used for the immunohistochemical identification of astrocytes and reactive astrocytes include glutamine synthetase and S100ÎČ [37,38], but these molecules are not exclusive to astrocytes.…”
Section: Discussionmentioning
confidence: 99%